A standardized commissioning framework of Monte Carlo dose calculation algorithms for proton pencil beam scanning treatment planning systems. Issue 4 (4th February 2020) - Chang, Chih‐Wei; Huang, Sheng; Harms, Joseph; Zhou, Jun; Zhang, Rongxiao; Dhabaan, Anees; Slopsema, Roelf; Kang, Minglei; Liu, Tian; McDonald, Mark; Langen, Katja; Lin, Liyong
Abstract : Purpose: Treatment planning systems (TPSs) from different vendors can involve different implementations of Monte Carlo dose calculation (MCDC) algorithms for pencil beam scanning (PBS) proton therapy. There are currently no guidelines for validating non‐water materials in TPSs. Furthermore, PBS‐specific parameters can vary by 1–2 orders of magnitude among different treatment delivery systems (TDSs). This paper proposes a standardized framework on the use of commissioning data and steps to validate TDS‐specific parameters and TPS‐specific heterogeneity modeling to potentially reduce these uncertainties. Methods: A standardized commissioning framework was developed to commission the MCDC algorithms of RayStation 8A and Eclipse AcurosPT v13.7.20 using water and non‐water materials. Measurements included Bragg peak depth‐dose and lateral spot profiles and scanning field outputs for Varian ProBeam. The phase‐space parameters were obtained from in‐air measurements and the number of protons per MU from output measurements of 10 × 10 cm 2 square fields at a 2 cm depth. Spot profiles and various PBS field measurements at additional depths were used to validate TPS. Human tissues in TPS, Gammex phantom materials, and artificial materials were used for the TPS benchmark and validation. Results: The maximum differences of phase parameters, spot sigma, and divergence between MCDC algorithms are below 4.5 µm and 0.26 mrad in air, respectively. Comparing TPS to measurements at depths, both MC algorithms predict the spot sigma within 0.5 mm uncertainty intervals, the resolution of the measurement device. Beam Configuration in AcurosPT is found to underestimate number of protons per MU by 2.5% and requires user adjustment to match measured data, while RayStation is within 1% of measurements using Auto model. A solid water phantom was used to validate the range accuracy of non‐water materials within 1% in AcurosPT. Conclusions: The proposed standardized commissioning framework can detect potential issues during PBS TPS MCDC commissioning processes, and potentially can shorten commissioning time and improve dosimetric accuracies. Secondary MCDC can be used to identify the root sources of disagreement between primary MCDC and measurement.